Synthesis of N-Sulfonylamidines by Catalyst-Free Hydroamination of Ynamides and Amines - Kong, Yulong; Yu, Lian; Cui, Yuming; Cao, Jian (Synthesis, 2014)
A novel synthesis of N-sulfonylamidines by catalyst-free hydroamination of N,N-disulfonyl ynamides with amines was developed. Alkyl amines react with N,N-disulfonyl ynamides under mild conditions, whereas aryl amines require higher temperatures. Plausible mechanisms are proposed to explain this reaction.
Keywords: amines; sulfonamides; aminations